2010
DOI: 10.1186/1471-2407-10-349
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens enterotoxin carboxy-terminal fragment is a novel tumor-homing peptide for human ovarian cancer

Abstract: BackgroundDevelopment of innovative, effective therapies against recurrent/chemotherapy-resistant ovarian cancer remains a high priority. Using high-throughput technologies to analyze genetic fingerprints of ovarian cancer, we have discovered extremely high expression of the genes encoding the proteins claudin-3 and claudin-4.MethodsBecause claudin-3 and -4 are the epithelial receptors for Clostridium perfringens enterotoxin (CPE), and are sufficient to mediate CPE binding, in this study we evaluated the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…Earlier, Cocco et al showed similar results using a fluorescein isothiocyanate-conjugated cCPE in models of ovarian cancer (15). However, the direct clinical translation of optical imaging approaches is limited by penetration depth of light, which is less than a couple of millimeters.…”
mentioning
confidence: 80%
“…Earlier, Cocco et al showed similar results using a fluorescein isothiocyanate-conjugated cCPE in models of ovarian cancer (15). However, the direct clinical translation of optical imaging approaches is limited by penetration depth of light, which is less than a couple of millimeters.…”
mentioning
confidence: 80%
“…Several studies have used the C-terminal fragment of CPE, fused with various cytotoxic drugs, to specifically kill tumor cells expressing claudin-3 and claudin-4 (16,49,50,52). This approach has also been successfully employed to target chemotherapy-resistant ovarian carcinomas or to reduce the formation of B16 melanoma cell-derived lung metastases (4,41). Based on these observations and our findings, we speculate that blocking peptides or neutralizing antibodies raised to the first extracellular loop of claudin-2 may be employed to limit the dissemination of cancer cells to the liver.…”
Section: Fig 10mentioning
confidence: 99%
“…Claudin-3 and claudin-4 are overexpressed in a range of human epithelial cell-derived tumors, including breast, prostate, ovarian, and pancreatic cancers (4). Interestingly, these tightjunctional proteins are bound by the Clostridium perfringens enterotoxin (CPE), which interacts with the second extracellular loop of claudin-3 (9).…”
Section: Fig 10mentioning
confidence: 99%
“…In addition to pancreatic cancer, claudin-4 is a potential target in chemotherapy-resistant ovarian cancer and other highly aggressive human epithelial tumors including breast and prostate cancer, making it attractive as a molecular imaging target. [23, 24] Moreover, targeting claudin-4 for therapy of PDAC was the subject of a recent review by Kojima et al and a number of studies describing claudin-4 as a target for molecular imaging have recently been reported. [25] Neesse et al assessed the ability of a naturally occurring peptide ligand for claudin-4 to detect tumors that overexpress claudin-4.…”
Section: Tumor Epithelial Cellsmentioning
confidence: 99%